A numerical study of thermo solutal melting - Scanlon, Thomas J. (Strojniški vestnik, 2005)
This paper describes the numerical investigation into the melting of a pure ice block into an aqueous solution of sodium carbonate (Na2CO3). The numerical study is concerned with capturing the evolving solid-fluid interface during phase change while solving sequentially the double-diffusive conditions resulting from the combined effects of thermal and solutal buoyancy in the flow field. The results show that, with a relatively simple phase change modelincorporated into a fixed grid, finite volume numerical formulation, reasonable concurrence may be obtained in comparison with published experimental data.
Keywords: prenos toplote; taljenje; dvofazni sistemi; dvokomponentni sistemi; led; light-emitting diode; raztopine; natrijev karbonat; modeliranje